Always Totalize! Perché abbiamo ancora bisogno della totalità (e della dialettica) - Gatto, Marco (L’ospite ingrato, 2021)
The article proposes a philosophical and historical reconstruction of a concept, “totality”, through the elaborations by Althusser, Sartre and Jameson. The aim is an analysis of the dissolution of “totality” as a philosophical category, grasped as a symptom of a more general crisis of Dialectic. As a possible resolution, the author proposes a neo-materialistic reading of “totality”, referring to the more recent theoretical considerations about the Marxism of the Real Abstraction, suggested by Roberto Finelli, and to some reconsidered arguments by Franco Fortini.